The Influence of Capital Size and Zakah on Islamic Social Reporting in Islamic Commercial Bank - M. Akbar Alfahrozi; Ridwansyah; Heni Verawati (Department of Islamic Banking, 2025)
Purpose – The objective of this study is to determine the impact of capital size and obligatory charity on Islamic Social Reporting in Sharia commercial banks. Methodology – The study’s population comprises 14 Islamic commercial banks, while the sample includes 9 Islamic commercial banks. This research employs an explanatory methodology and is quantitative in nature. Regression analysis of panel data, supported by Eviews 12 analysis tools, is the research methodology utilized in this work. Findings – The study’s findings revealed a significant positive correlation between the size of capital or a car and Islamic social reporting. This suggests that Islamic banks with substantial capital tend to be more effective in conducting social reports in a transparent and accountable manner, adhering to Islamic principles. Conversely, the study indicated that zakah has a minimal impact on Islamic social reporting. It further asserted that zakah’s contribution to corporate social reporting is not as substantial as other factors, such as other capital resources, which enable companies to conduct social reporting comprehensively and systematically. Implications – While Indonesia’s Islamic banking industry is experiencing growth and intensifying competition, maintaining a certain level of bank health remains essential. A bank’s capital is one of several key factors that determine its health, as it is primarily responsible for generating the highest possible returns. Originality – In addition to fulfilling legal obligations, Islamic banks’ implementation of the Islamic Social Reporting Program surpasses expectations by establishing a robust Islamic philosophy and tasawwur (visual representation) as the foundation for their social responsibility. This positioning elevates them as one of the financial institutions that can contribute to the flourishing of the community.